Study of High Waves and Sea Level during Marian Tropical Cyclone in Southern Sea of Java - Ahmad Fadlan; Rijal Sainsfikri (Jurnal Perikanan dan Kelautan, 2023)
The southern coastal area of Java is an area directly bordering the Indian Ocean. This area often experiences high waves, which have an impact on community activities in coastal areas. High waves on the south coast of Java generally occur due to the impact of the Australian monsoon and tropical cyclones that form in the Indian Ocean. One of the tropical cyclones that emerged was Tropical Cyclone Marian, which occurred from February 27 to March 5, 2021. This research will use the Delft3D model, reanalysis, and observational data to determine these conditions. Based on the analysis results, the Delft3D Model can simulate tidal patterns and wave height conditions that occurred during the Mariana Tropical Cyclone in the Southern Java Waters region, supported by an RMSE correction of 0.2 to 0.4. The model results also show that in spatial conditions, there are fluctuations in sea level and wave height when cyclones occur, indicating that cyclones have sufficiently affected sea level and wave height conditions, which are supported by a comparison chart that shows sea level conditions tend to be higher than normal conditions and the model results. The wave height has fluctuations, indicating that the wave height corresponds to the cyclone period